A review on the role of MiR-193a-5p in oncogenesis and tumor progression - Tang, Weixiang; Rao, Yuhua; Pi, Longsheng; Li, Jinping (Frontiers in Oncology, 2025)
MicroRNA (miRNA), a class of short non-coding RNA molecules comprising 18-25 nucleotides, are pivotal regulators of gene expression within physiological environments, influencing processes such as cell growth, apoptosis, proliferation, differentiation, migration (including cellular movement), and angiogenesis. They also play a crucial role in disease progression, invasion, and metastasis. Specifically, miR-193a-5p, a member of the miR-193a family, is instrumental in the development of various malignancies, including osteosarcoma, hepatocellular carcinoma, cervical cancer, melanoma, gastrointestinal cancer, lung cancer, prostate cancer, and bladder cancer. Studies have revealed that miR-193a-5p (sequence: UGGGUCUUUGCGGGCGAGAUGA; accession number: MIMAT0004614) is downregulated in numerous cancer cell lines and clinical samples. Furthermore, the tumor-suppressive effects of miR-193a-5p have been corroborated in animal models across different cancer types. These studies suggest that overexpression of this miRNA or modulation of lncRNA expression can inhibit oncogenesis. In this review, we summarize the functions of miR-193a-5p in cancer development.